Liver Anatomy, Histochemistry, and Ultrastructure of Eupemphix nattereri (Anura: Leiuperidae) During the Breeding Season - Franco-Belussi, Lilian [UNESP]; de Souza Santos, Lia Raquel; Zieri, Rodrigo [UNESP]; Vicentini, Carlos Alberto; Taboga, Sebastiao Roberto [UNESP]; de Oliveira, Classius [UNESP] (Zoological Soc Japan, 2012)
The arrangement of the hepatic tissue is directly related to physiological characteristics of animals, such as ectothermy, diet, and reproductive status. Here, we describe the anatomy, histology, and ultrastructure of the liver in adult males of Eupemphix nattereri during the breeding season. The liver is an organ with an irregular shape, red in color, and occupies a large portion of the body cavity. Anatomically, it is divided into three lobes: right, mid, and left. Further subdivision into lobules is not observed. A thin capsule of connective tissue covers externally the organ, which is responsible for its support and protection. The hepatic parenchyma is formed by two layers of polyhedral-shaped hepatocytes arranged in a double cordon. These cordons are filled with hepatic sinusoids that greatly vary in size and are closely associated with hepatocytes. There are also bile canaliculi and immune cells between hepatic cordons-the melanomacrophages. These canaliculi are covered with short microvilli, which protrude into the lumen. Melanomacrophages have several cytoplasmic substances, such as melanin, lipofuscin, and hemosiderin, which form due to liver metabolism and contribute to the typical coloration of the organ. A large amount of mitochondria and other organelles, such as a well-developed Golgi apparatus, smooth endoplasmic reticulum, and abundant glycogen are found in the cytoplasm of hepatocytes.
Keywords: Liver; Eupemphix nattereri; hepatocytes; Melanomacrophages; lipofuscin; hemosiderin